FDI And Economic Growth Relationship In Sub-Saharan Africa: Is The Domestic Financial System A Significant Intermediator? - Olagbaju, Ifeolu Oladiran; Akinlo, Anthony Enisan (Archives of Business Research, 2018)
This paper contributes to the literature on the effect of Foreign Direct Investment (FDI) on economic growth by examining the role of financial development as a source of absorptive capacity in the FDI-economic growth relationship in Sub-Saharan Africa (SSA). Using panel data econometric techniques and an unbalanced dataset of 1989-2013, we examine the independent effect of FDI on economic growth, as well as the impact of an interactive relationship between FDI and financial development on economic growth in SSA. We find that FDI does not directly lead to economic growth in SSA. However, the financial system through banking sector development enhances the effect of FDI on economic growth in the region. This finding is linked to the existence of a causal relationship between banking sector development and FDI, which is stronger in the low-income subsample relative to the middle-income subsample and the full SSA sample. We also estimate the threshold financial development levels essential for the expected FDI-economic growth effect to occur. Finally, the study recommends that strategies toward the attraction of foreign capital in SSA must be complemented by measures to develop the domestic financial system.